Collaborative Planning for Radical Innovation: Lessons from a Health Care Region in Denmark - Bruun Hansen, Karsten; Boch Waldorff, Susanne (Scandinavian Journal of Public Administration, 2020)
In this paper, we explain the challenges that emerged when a Danish region tried to employ innovation planning structures, without taking into account already existing governance paradigms in the organisation. We present a qualitative case study of a large regional health organisation in Denmark, which in 2016–2017 had the aim of fostering collaborative innovation. Drawing upon the concept of governance paradigms, we analyse how the strategic initiative and planning process, which used collaborative design thinking methods, in line with the New Public Governance paradigm, was hampered and finally rejected by managers embedded in an organisational context dominated primarily by the New Public Management and Traditional Public Administration paradigms.